Management of late implantable cardiac device infection in the elderly patient: a case report - Ronald Winardi Kartika (Journal of International Surgery and Clinical Medicine, 2022)
Introduction: Currently, the use of Cardiac Implantable Electronic Devices (CIED) is widely used, but in line with the increase in the use of CIEDs, there has also been an increase in the rate of complications. Infection accounts for about 1% of them. All of these were seen in chronically ill patients with multiple comorbid conditions within a few years of implantation. It has not become a standard treatment for infection in the pacemaker bag until now. This study aims to report an immunocompetent patient who developed a pacemaker pocket infection with Escherichia coli bacteria after more than 10 years post-implantation who was successfully treated by moving the bag more medial to sterilization on a pacemaker battery. Case Report: We report an 89 year-old, elderly patient with sick sinus syndrome with a pacemaker pocket infection. The method we used was to explant the battery from the pacemaker and sterilize it with gas, the next day it was reassembled by moving the bag more medially. Loading of the vancomycin antibiotic was carried out for 14 days while still controlling the renal function Conclusion: Staphylococcus aureus causes the majority of CIED infections, especially in immunocompromised elderly patients. Proper treatment of infected pacemaker pouches is necessary with minimal improvement on antibiotics. If left untreated, it can develop into endocarditis which has a high mortality rate.